Modifikasi dan Uji Kinerja Alat Pengering Tipe Rak Model Teta 22 Biji Pala (Myristica Fragrans Houtt) Menggunakan Sumber Panas Gas LPG - Nofri Abdul Azis Amiri; Ireine Longdong; Dedie Tooy (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The research is aimed at: 1. Modified the teta '17, 2 model rack dryer. Testing instrument performance includes temperature, air humidity, water levels and the drying rate of water. The study is conducted using experimental methods for tooling and data analysis using descriptive methods that the data from observation is compiled in the form of a chart, then described in graph form, and described. Each rack of the top shelf and lower shelf each USES 500 nutmeg samples. Each experiment was performed 2 (two) times a test. The observed variables are temperature, humidity, water content and drying rate. The results of this study have modified the teta '17 model rack dryer by adding a chimney to no condensation on the surface of the instrument wall. Based on the average, the top temperature temperature is 53rd and the lower shelf average, at 55 plenum, and the average temperature in plenum is 54 plenum. The average air humidity in plenum is 70%. The average high levels of nutmeg water amount to 10.2% and bottom shelf 8.7%. The curing time it takes to dry the nutmeg to a water level of 8-10% is 11 hours. The rate of drying off the water level of deuteronomy 1 top shelf by 2.55%, bottom shelf 2.72% and 2.65% top shelf by 2.65%, bottom shelf by 2.75%.